PENERAPAN MODEL PEMBELAJARAN SENTRA DALAM PENGEMBANGAN KECERDASAN BAHASA EKSPRESIF ANAK USIA DINI - Farny Sutriany Jafar; Malpaleni Satriana (Universitas Negeri Makassar, 2018)
This study aims to describe: (1) implementation of a learning model center in the development of expressive language of early childhood, and (2) The factors that influence the development of early childhood expressive language in the center learning model. The method used is qualitative research with a case study approach. Data collection techniques were carried out using: (1) Field observations to observe all activities carried out in TK Negeri 01 Tenggarong, (2) Methods of interviews conducted by teachers, students and principals of TK Negeri 01 Tenggarong, (3) Method of documentation, as supporting to obtain data in the field, and from the documentation / recording results are transcribed and grouped and then analyzed using a flow model, which starts with (a) data reduction, (b) data presentation, (c) conclusions. The results showed that: (1) the center learning model was instrumental in developing children's expressive language intelligence, because children can learn to communicate with other people in various ways, children are also able to express feelings, ideas with appropriate word choices when communicating (2) factors that influence the development of expressive language of early childhood in the center learning model are: health factors, intelligence factors, family socioeconomic status, gender, and family relationships.